Facile Preparation of Silk Fibroin Scaffold Via Direct Solvent Exchange (Journal of Fiber Bioengineering and Informatics, 2023)
Although silk fibroin (SF) materials have gained extensive attention in tissue engineering due to theirgood machinability, biocompatibility, biodegradability, the complex processes, unmatched pore structures,and chemical crosslinker still hinder their mass production and clinic use. In this study, we reported adirect green and high-efficiency process to fabricate 3D silk fibroin scaffold by solvent exchange in water.The pore parameters were easily regulated with NaCl as auxiliary porogen. More importantly, withoutusing any crosslinker or organic chemical-induced crystallin, SF scaffolds is mainly constructed withstable silk II crystalline (constituent with β-sheets), which was confirmed by Flourier transform infraredspectroscopy (FTIR) and X-ray diffraction (XRD). Additionally, the scaffold in our research keeps goodtunability on mechanical properties, which has been demonstrated by the results of mechanical testingand provides a feasible way to optimize physical cues for further applications. Thus, the 3D poroussilk scaffold with high efficiency and promising structures broaden the potential as a substitute forbiomaterials.